From “Green Building” to Architecture Integrated with Nature. The Principle of Using Natural Forms - Logvinov, Victor; Ponomareva, Irina (project baikal, 2017)
As a follow-up to the theme of integration between architecture and nature started in the previous issues of Project Baikal (PB 49, 50, 51), the article reviews the principle of using natural forms and also features the history and the current state of the ideas and practices based on imitation and representation of natural forms in architecture. The author analyses the natural basis for using of orthogonal geometry in architecture and reviews utilization of nonlinear geometry with the elements of randomness in the world and national practice.